The Influence of Work Motivation and Compensation on Employee Performance in PT Delami Brands Kharisma Busana Surabaya - Nur Laili Safitri; R. Agus Baktiono; Elok Damayanti; I Gede Arimbawa (Yayasan Ahmar Cendekia Indonesia, 2021)
This study aims to determine the effect of work motivation and compensation on the performance of PT. Delami Brands Kharisma Busana Surabaya. This study used a quantitative approach and data collection through questionnaires and observations. With a population of 76 respondents. Analysis of the data used the validity test, reliability test, classic assumption test, and multiple linear analysis test. The results showed that the effect of work motivation and compensation on the performance of PT. Delami Brands Khasrisma Busana Surabaya showed positive and significant results. The F test results are 70,878> F table = 2,92 simultaneously. Partially work motivation of 8.433> t table 1.993 has a significant effect on employee performance, compensation of 4.564> 1.993 has a significant effect on the performance of employees of PT. Delami Brands Kharisma Busana Surabaya.